Undercover : Police Surveillance in America. - Marx, Gary T. (University of California Press, 1988)
Providing a rich picture of past and present undercover work, and drawing on unpublished documents and interviews with the FBI and local police, this penetrating study examines the variety of undercover operations and the ethical issues and empirical assumptions raised when the state officially sanctions deception and trickery and allows its agents to participate in crime.